A decomposition of the black-white differential in birth outcomes - M. Melinda Pitts; Mary Beth Walker; Brian S. Armour (Federal Reserve Bank of Atlanta, 2011)
Substantial racial disparities continue to persist in the prevalence of preterm births and lowbirth-weight births. Health policy aimed at reducing these disparities could be better targeted if the differences in birth outcomes are better understood. This study decomposes these racial disparities in birth outcomes to determine the extent to which the disparities are driven by differences in measurable characteristics of black mothers and white mothers as well as the extent to which the gap results from differences in the impact of these characteristics. The analysis is focused on three adverse birth outcomes: preterm, early preterm birth (less than 32 weeks gestation), and low birth weight. The results suggest that differences in covariates accounted for approximately 25 percent of the gap in the incidence of preterm births. The specific characteristics that matter the most are marriage rates, father's characteristics, and prenatal care. For gestation-adjusted birth weight, approximately 16 percent of the racial gap for first births is explained by covariates; for subsequent births this covariate explanation rises to 22 percent of the gap. Furthermore, differences in coefficients explain about another quarter of the gap in preterm birth outcomes but very little of the gap in birth weight.
Keywords: I1; 330; racial disparities; preterm birth; low birth weight